2021
DOI: 10.1177/1078155221992103
|View full text |Cite
|
Sign up to set email alerts
|

Surface contamination with nine antineoplastic drugs in 109 canadian centers; 10 years of a monitoring program

Abstract: Introduction Healthcare workers exposure to antineoplastic drugs can lead to adverse health effects. Guidelines promote the safe handling of antineoplastic drugs, but no safe exposure limit was determined. Regular surface sampling contributes to ensuring workers safety. Methods A cross-sectional monitoring is conducted once a year with voluntary Canadian centers, since 2010. Twelve standardized sampling sites were sampled. Samples were analyzed by high performance mass coupled liquid chromatography. The limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 35 publications
4
21
1
Order By: Relevance
“…Similar conclusions were also published by (Schierl et al 2009) from 102 German hospitals. On the contrary, a recent study by Canadian authors (Chabut et al 2021) based on 1217 samples from 109 centers showed that workplaces with the annual number of ADs preparations above 5 000 (i.e., above 400 monthly preparations to compare with our study; cf Table 1) had higher surface concentrations of CP. Similarly, Palamini et al (2020) concluded that higher numbers of CP preparations result in higher CP surface contamination, and the correlation with numbers of AD preparations was also reported in a study of 24 Swiss hospital pharmacies (Fleury-Souverain et al 2015).…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…Similar conclusions were also published by (Schierl et al 2009) from 102 German hospitals. On the contrary, a recent study by Canadian authors (Chabut et al 2021) based on 1217 samples from 109 centers showed that workplaces with the annual number of ADs preparations above 5 000 (i.e., above 400 monthly preparations to compare with our study; cf Table 1) had higher surface concentrations of CP. Similarly, Palamini et al (2020) concluded that higher numbers of CP preparations result in higher CP surface contamination, and the correlation with numbers of AD preparations was also reported in a study of 24 Swiss hospital pharmacies (Fleury-Souverain et al 2015).…”
Section: Discussioncontrasting
confidence: 84%
“…On the other hand, the pharmacy areas outside the preparation (dispatch areas or storage rooms) were more contaminated in SK compared to the CZ. This confirms that a significant reduction in contamination in the CZ can be achieved through the implementation of complex management measures including regular monitoring (Chabut et al 2021;Kiffmeyer et al 2013;Yoshida et al 2013), preventive and corrective measures such as the use of zones, adjusted cleaning procedures (Odraska et al 2013), regular training of pharmaceutical staff (Odraska et al 2014;Ozakin et al 2019), or using of closed drug transfer devices (Siderov et al 2010).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations